Density form factors of the 1D Bose gas for finite entropy states. (25th February 2015) - De Nardis, J; Panfil, M
Abstract: We consider the Lieb–Liniger model for a gas of bosonic δ -interacting particles. Using Algebraic Bethe Ansatz results we compute the thermodynamic limit of the form factors of the density operator between finite entropy eigenstates such as finite temperature states or generic non-equilibrium highly excited states. These form factors are crucial building blocks to obtain the thermodynamic exact dynamic correlation functions of such physically relevant states. As a proof of principle we compute an approximated dynamic structure factor by including only the simplest types of particle-hole excitations and show the agreement with known results.